Iron deficiency anemia among rural population attending tertiary care teaching hospital - Dr. Sharadamani. G.S. (Tropical Journal of Pathology and Microbiology, 2017)
Background: Nutritional anemia is a major public health problem in India and is primarily due to iron deficiency which is more common among rural population. The present study aimed at evaluating iron deficiency anemia among rural population attending our tertiary care teaching hospital.Materials and Methods: Patients having hemoglobin level below 11g/dl with Serum Iron level <30 ug/dl and/or serum TIBC>400 ug/dl were enrolled in the study. A total of 259 patients were included in the study. Hemoglobin estimation and other investigations were performed as per standard protocol in pathology laboratory.Results: Majority of patients were females (58.69%) and preponderance of iron deficiency anemia was seen in the age group of 21-30(28.96%) followed by 31-40(25.09%). Majority of male patients had mild anemia (55.14%) whereas majority of females had moderate anemia (57.24%).Conclusion: Iron deficiency anemia is significantly high among women of reproductive age group. Among females moderate anemia was predominant. Mild anemia was commonly observed in males.